2011
DOI: 10.1016/j.placenta.2011.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated progenitor cells: An under-recognized potential source of stem cells in maternal lung

Abstract: Novel therapies are needed for the treatment of acute and chronic lung diseases, many of which are incurable. The use of exogenous stem cells has shown promise in both animal models and clinical trials. However, to date, the stem cell literature has under-recognized naturally acquired pregnancy-associated progenitor cells (PAPCs). These cells are found at sites of injury or disease in female tissues. They persist for decades after parturition in maternal blood and organs, with the largest number being found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
(91 reference statements)
1
19
0
Order By: Relevance
“…Clinical Study V Cirello and others Microchimerism in autoimmune thyroid diseases to target diseased tissue (40,41,42). Consistently in the GD cases in the present study, male cells were documented to 'travel' into a blood vessel and were found interposed between female cells and forming follicles in the thyroid.…”
Section: European Journal Of Endocrinologysupporting
confidence: 87%
“…Clinical Study V Cirello and others Microchimerism in autoimmune thyroid diseases to target diseased tissue (40,41,42). Consistently in the GD cases in the present study, male cells were documented to 'travel' into a blood vessel and were found interposed between female cells and forming follicles in the thyroid.…”
Section: European Journal Of Endocrinologysupporting
confidence: 87%
“…There has been great interest in whether these exogenously derived stem cells prevent or ameliorate various types of lung injuries. None of these studies, however, consider or indeed even acknowledge the potential presence of fetal cells in the adult lung [25]. The results presented here, in conjunction with those of previous studies that demonstrate the possible involvement of pregnancy-associated progenitor cells in maternal tissue repair [9,12,17], suggest that the naturally acquired population of fetal cells should be considered in any studies investigating the role of stem cells in the lung.…”
Section: Discussionmentioning
confidence: 52%
“…MSCs are stromal cells characterized by an absence of hematopoietic lineage markers, in vitro adherence to plastic, and their ability to differentiate into adipocytes, chondrocytes, and osteocytes [34]. We have previously suggested that fetal cells in the maternal organs may be MSCs [35]. Earlier work from our laboratory showed expression of surface markers on fetal cells that were characteristic of MSCs [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…These isolated fetal cells were able to differentiate in vitro into adipocytes and osteocytes. Furthermore, microchimeric fetal cells are known to differentiate in vivo in response to injury in both mice and humans, contributing to repair of injury in multiple maternal organs, demonstrating pluripotency [16,35]. The possibility that the MSCs and placental cells are the same population cannot be excluded, as the placenta is known to contain MSCs [37].…”
Section: Discussionmentioning
confidence: 99%